The past as a foreign country?: some methodological implications of doing historical criminology - Bosworth, Mary (The British journal of criminology, 2001)
This article describes methodological issues that arose from the author's research on early modern women's imprisonment in order to reflect on broader questions about how crime and punishment are studied. She demonstrates that the ways in which a criminologist interprets his or her data, what evidence exists, and the emotional repercussions of writing on crime and punishment reveal the researcher's ethical stance towards his or her subjects and the allegiances he or she creates with them. These problems of interpretation, evidence and emotion transcend time and culture and are built into the research goals of the discipline of criminology itself